A Heuristic Approach Based on Clarke-Wright Algorithm for Open Vehicle Routing Problem. (5th December 2013) - Pichpibul, Tantikorn; Kawtummachai, Ruengsak
Abstract : We propose a heuristic approach based on the Clarke-Wright algorithm (CW) to solve the open version of the well-known capacitated vehicle routing problem in which vehicles are not required to return to the depot after completing service. The proposed CW has been presented in four procedures composed of Clarke-Wright formula modification, open-route construction, two-phase selection, and route postimprovement. Computational results show that the proposed CW is competitive and outperforms classical CW in all directions. Moreover, the best known solution is also obtained in 97% of tested instances (60 out of 62).